2020
DOI: 10.26599/bsa.2020.9050009
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative neurophysiological monitoring in selective dorsal rhizotomy (SDR)

Abstract: For decades, intraoperative neurophysiological monitoring (IONM) has been used to guide selective dorsal rhizotomy (SDR) for the treatment of spastic cerebral palsy (CP). Electromyography (EMG) interpretation methods, which are the core of IONM, have never been fully discussed and addressed, and their importance and necessity in SDR have been questioned for years. However, outcomes of CP patients who have undergone IONM-guided SDR have been favorable, and surgery-related complications are extremely minimal. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…We made measurements on 21 patients before and after sedation and during the transition period from alertness to sedation under general anesthesia. As anesthesia suppressed neural reflex excitation ( Fee and Miller, 2004 ; Jiang et al., 2020 ), this study facilitated self-consistent comparisons to separate the neural and structural contributions to spasticity, which until now these contributions have been very challenging to differentiate but are very important for identifying the underlying origins of spasticity and symptom management ( Fee and Miller, 2004 ; Smith et al., 2011 ; Sinkjær and Magnussen, 1994 ). For example, it has been suggested that spasticity in patients with predominantly hyperactive reflexes was likely to respond well to functional electrical stimulation, whereas other patients responded less well to the same stimulation therapy ( Alhusaini, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…We made measurements on 21 patients before and after sedation and during the transition period from alertness to sedation under general anesthesia. As anesthesia suppressed neural reflex excitation ( Fee and Miller, 2004 ; Jiang et al., 2020 ), this study facilitated self-consistent comparisons to separate the neural and structural contributions to spasticity, which until now these contributions have been very challenging to differentiate but are very important for identifying the underlying origins of spasticity and symptom management ( Fee and Miller, 2004 ; Smith et al., 2011 ; Sinkjær and Magnussen, 1994 ). For example, it has been suggested that spasticity in patients with predominantly hyperactive reflexes was likely to respond well to functional electrical stimulation, whereas other patients responded less well to the same stimulation therapy ( Alhusaini, 2013 ).…”
Section: Introductionmentioning
confidence: 99%